2020
DOI: 10.1080/1369183x.2020.1839398
|View full text |Cite
|
Sign up to set email alerts
|

Migration uncertainty in the context of Brexit: resource conservation tactics

Abstract: The Brexit referendum has led to uncertainty, which has threatened EU migrants' resources, including their rights to reside, to run a business or access welfare. Cross-national political and legal resources that include citizenship rights can enable migrants' access to health care, pensions, education and other welfare benefits, but these remain far from guaranteed. Using Conservation of Resources theory, we show how coping with uncertainty requires the mobilisation of individual and collective resources. We d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Japanese are therefore more likely to seek cross-generational and crosscultural support, maximizing the local resources that their informal networks as well as commercial services can offer. We may see similar patterns among the British IRM community in Spain over the coming years as a result of Brexit which has created considerable uncertainty and anxiety, especially in relation to the ongoing exportability of welfare rights (Hall et al 2020). We can also refer to the impact of other structural changes, including the 2011 earthquake in Japan that triggered a rapid increase in emigration, and the more recent COVID-19 pandemic that may impact on the security of Japanese and British IRMs as they make decisions around whether to age in place or return to the home country.…”
Section: Discussionmentioning
confidence: 78%
“…Japanese are therefore more likely to seek cross-generational and crosscultural support, maximizing the local resources that their informal networks as well as commercial services can offer. We may see similar patterns among the British IRM community in Spain over the coming years as a result of Brexit which has created considerable uncertainty and anxiety, especially in relation to the ongoing exportability of welfare rights (Hall et al 2020). We can also refer to the impact of other structural changes, including the 2011 earthquake in Japan that triggered a rapid increase in emigration, and the more recent COVID-19 pandemic that may impact on the security of Japanese and British IRMs as they make decisions around whether to age in place or return to the home country.…”
Section: Discussionmentioning
confidence: 78%
“…When [husband] died his niece … said, 'Anne don't be on your own, come and live with us [in the UK]', which was nice of her, and I'm sure that if the worst came to the worst I could go and live in their house. (Anne,74,widowed) Decisions to return were also influenced by broader social and legal structures, including Brexit, previously referred to as an 'unsettling event' that has created considerable uncertainty and precarity for migrants, particularly around their social protection (Kilkey and Ryan, 2021;Hall et al, 2020). Whilst the Withdrawal Agreement has secured IRM rights to health care, pension increments and other welfare entitlements (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Brexit and COVID-19 are also likely to have exacerbated care precarity. Brexit was an 'unsettling event', introducing significant uncertainty into the lives of EU migrants, particularly in relation to the potential loss of welfare rights (Hall et al, 2020). Whilst the rights of those who moved to another EU country (and became legally resident) by 31 December 2020 have been secured under the Withdrawal Agreement, the same rights will not be available to those who move from January 2021.…”
Section: Discussionmentioning
confidence: 99%
“…As such, many EU migrants could have interpreted the Brexit vote as a rejection of their presence in the UK. Moreover, the referendum result was accompanied by uncertainty about the future social rights of EU migrants in the UK (Hall et al 2020; McGhee, Moreh, and Vlachantoni 2017). 2 Some evidence indicated that the referendum increased social anxiety among EU migrants (Frost 2020; Guma and Dafydd Jones 2019).…”
Section: Conceptual Backgroundmentioning
confidence: 99%